Advanced injectable hydrogels for cartilage tissue engineering - Zhu, Senbo; Li, Yong; He, Zeju; Ji, Lichen; Zhang, Wei; Tong, Yu; Luo, Junchao; Yu, Dongsheng; Zhang, Qiong; Bi, Qing (Frontiers in Bioengineering and Biotechnology, 2022)
The rapid development of tissue engineering makes it an effective strategy for repairing cartilage defects. The significant advantages of injectable hydrogels for cartilage injury include the prop-erties of natural extracellular cartilage matrix (ECM), good biocompatibility, and strong plasticity to adapt to irregular cartilage defect surfaces. These inherent properties make injectable hydrogels a promising tool for cartilage tissue engineering. This paper reviews the research progress on advanced injectable hydrogels. The cross-linking method and structure of injectable hydrogels are thoroughly discussed. Furthermore, polymers, cells, and stimulators commonly used in the preparation of injectable hydrogels are thoroughly reviewed. Finally, we summarize the research progress of the latest advanced hydrogels for cartilage repair and the future challenges for in-jectable hydrogels.